2011
DOI: 10.1002/nau.21042
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of parasympathetic postganglionic neurons and bladder detrusor muscle directly after sacral root transection and repair using nerve transfer

Abstract: Aims-This is a continuation of studies examining the effectiveness of root repairs and nerve transfers for bladder reinnervation. Our previous retrograde fluorogold tracing studies from the bladder to the spinal cord found regrowth of axons from the spinal cord through the nerve repair site to the bladder which was confirmed electrophysiologically (Ruggieri et al., 2006). The current study determines whether the pattern of axonal regrowth from the repaired nerves or roots to the bladder is different between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…6,7,20,27,30 There are several recent reports of successful somatic nerve transfers in animal models and in patients for restoration of bladder function. 3,4,9,10,14,19-22,26,31 We found, using a canine model, that bladder reinnervation after sacral ventral root transection can be achieved by nerve transfer and surgical coaptation of coccygeal roots to the severed sacral roots, or transfer of genitofemoral nerves to the pelvic nerve as evidenced by increased bladder pressure upon functional electrical stimulation of these nerves after time had elapsed for reinnervation. In the majority of animals in each group, effective detrusor contractions were elicited with stimulation of the reinnervated pelvic nerve.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…6,7,20,27,30 There are several recent reports of successful somatic nerve transfers in animal models and in patients for restoration of bladder function. 3,4,9,10,14,19-22,26,31 We found, using a canine model, that bladder reinnervation after sacral ventral root transection can be achieved by nerve transfer and surgical coaptation of coccygeal roots to the severed sacral roots, or transfer of genitofemoral nerves to the pelvic nerve as evidenced by increased bladder pressure upon functional electrical stimulation of these nerves after time had elapsed for reinnervation. In the majority of animals in each group, effective detrusor contractions were elicited with stimulation of the reinnervated pelvic nerve.…”
Section: Introductionmentioning
confidence: 85%
“…4,21,22 Anterograde axonal tracing also confirmed regrowth of axons from the genitofemoral nerve into the bladder detrusor muscle after these heterotopic somatic nerve transfers. 3 …”
Section: Introductionmentioning
confidence: 99%
“…In the normal bladder, all axons in the pelvic nerve innervate intramural postganglionic (parasympathetic) ganglia cells; 24 this pathway is not blocked by SCh. However, the new neuronal pathway, achieved by either GFNT or FNT, is blocked by SCh.…”
Section: Discussionmentioning
confidence: 99%
“…19, 34, 35 In an initial study using intercostal nerves as donor nerves in one dog, 35 the immediate postoperative recovery was poor. We next examined the feasibility of transferring the ilioinguinal or iliohypogastric nerves, but each was too short to reach the bladder base.…”
Section: Strategies For Bladder Reinnervationmentioning
confidence: 99%
“…We have previously found that transfer of the genitofemoral nerve (a mixed somatic sensory and motor nerve) to the pelvic nerve leads to innervation of neurons of intramural ganglia, as well as direct innervation of smooth muscle fibres. 19 However, the end organ targets after transfer of other nerve types have yet to be examined. Lastly, the types of receptors activated by the transferred nerves for storage and voiding reflexes need to be determined in physiological studies.…”
Section: Future Researchmentioning
confidence: 99%